If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(k-7.2k)=(-k-1.k+2)
We move all terms to the left:
(k-7.2k)-((-k-1.k+2))=0
We add all the numbers together, and all the variables
(-6.2k)-((-2k+2))=0
We get rid of parentheses
-6.2k-((-2k+2))=0
We calculate terms in parentheses: -((-2k+2)), so:We get rid of parentheses
(-2k+2)
We get rid of parentheses
-2k+2
Back to the equation:
-(-2k+2)
-6.2k+2k-2=0
We add all the numbers together, and all the variables
-4.2k-2=0
We move all terms containing k to the left, all other terms to the right
-4.2k=2
k=2/-4.2
k=-1/2.1
| 3(2x+1)+4=16 | | 10y-25=5(2y-5) | | 14p=17+15p | | 2n-7=-8n+13 | | 5m-12=2m-3 | | 19y+11=20y-16 | | 8×-2=-97x | | 5x/3-2/3=4x/2+1/2 | | 13z-18z=15 | | 4(m+12)=20 | | 55x-3(9x)+12(=64) | | 2x^2-2x-180=02x2−2x−180=0 | | -21=u/9 | | −6(x+2)+3(x−4)=x+4+4 | | 16w-10w=18 | | 320=x*x | | 3(4x+3)+4=3- | | 1/5x1=1 | | 0=-3x+8+2 | | x+9/6=x-6/3 | | 2(2x+4)=1/2(24-12x) | | -184=8(-5v+7) | | .10x+1.8=0.9(9+x) | | 43=8y | | (x+3)-(2x-4)=3x-5 | | 7+3(1-2x)=x | | 2n-7=8n+13 | | 8/x-5=3/6 | | 0.5(x+12)=8+0.75(x–28) | | 4+10=-2(4x-7) | | 80-n=-54 | | 3/5(x+2=x-4 |